ANALISIS PEMANENAN AIR HUJAN (STUDI KASUS DI KAMPUS UNTAG SEMARANG) - Nicko Fadhil Muhammad (Journal of Civil Engineering and Technology Sciences, 2022)
Human needs for vital living air, ranging from ablution, bathing, washing, latrine, cooking, washing, and so on. The limitation of clean water from PDAM is a necessity, because to meet the air needs of every resident who needs abundant raw water and adequate infrastructure. UNTAG Semarang campus which is located on Jl. Pawiyatan Luhur, Bendan Duwur Village, Gajahmungkur District, Semarang City has 7 main buildings. All of these buildings have daily water needs for toilets, ablution and watering plants around the buildings. The highest potential for rainwater harvesting at the UNTAG Semarang Campus is in February with the following potential catches: Faculty Building 233 m3, Fisip & FTP Building 211 m3, Faculty & Rectorate Building 321 m3, FEB & YPP 17 Building 229 m3, Rusunawa Building is 48 m3, Campus Mosque is 26 m3 and PMB Building & Library is 48 m3.